Rancangan Pengembangan Ekowisata Bukit Matoa di Kota Padang, Aspek Kesehatan dan Keselamatan Kerja, dan Lingkungan (K3L) - Gina Syakila Intania; Hanifa Zahra; Silvia Maharani Wineti; Syarifa Ayuni; Yoshiana Safira; Randy Novirsa (Warta Pengabdian Andalas, 2023)
Ecotourism is a tourism development concept that promotes tourism that is friendly to environmental and cultural sustainability and impacts the local economy. As part of the strategic area for tourism development in Indonesia, Bukit Matoa, Kelurahan Mata Air, West Sumatra has the potential to be developed as an ecotourism area. Based on a field survey, the group discovered that Matoa Hill still required additional development from numerous perspectives, particularly in occupational health and safety (OHS) and environmental health, to become an ecotourism area. The methods used in this project were interviews, observation, documentation, and literature studies. From the results, it was found that in the environmental health aspect, it was found that the availability of clean water and environmental sanitation facilities was inadequate. So, the group prepared a Bukit Matoa ecotourism plan regarding the OHS and environmental health to become a reference for the local government in planning, implementing and developing ecotourism. It hopes the development activities of Bukit Matoa can be more focused and planned.